RISK FACTORS PRETERM DELIVERY. MATERNAL PERINATAL INSTITUTE - Villamonte, Wilfredo (2015)
OBJETIVE: To determine the risk factors of preterm birth. DESIGN. Case control study. Setting: Maternal Perinatal Institute during the first trimester of 1996. MATERIAL AND METHODS: One hundred and sixty-five patients with preterm birth and 330 controls. RESULTS: The absence of prenatal control (OR= 14,4 and P < 0,01), born in the highland (OR= 2,26; P= 0, 001) and jungle (OR= 3,33; P= 0, 013), living in a poverty district (OR= 2,52; P= 0,05), previous preterm births (OR= 1,62; P< 0,05), obstetrical diagnosis of third trimester hemorrhage (OR= 17,33; P= 0, 00001), preterm rupture of membranes (OR= 7,29; P = 0,000001), acute fetal distress (OR= 3,63; P= 0, 005), breech presentation (OR=2,89; P= 0,021), preeclampsia (OR=1,92; P= 0,05) and twin pregnancy (OR= 2,26; P= 0, 09) were risk factors for preterm birth. CONCLUSIÓN: Third trimester hemorrhage, preterm rupture of membranes, acute fetal distress, preeclampsia and twin pregnancy were risk factors forpreterm birth.